A novel rhein-huprine hybrid ameliorates disease-modifying properties in preclinical mice model of Alzheimer’s disease exacerbated with high fat diet - Triana Espinosa-Jiménez; Amanda Cano; Elena Sánchez-López; Jordi Olloquequi; Jaume Folch; Mònica Bulló; Ester Verdaguer; Carme Auladell; Caterina Pont; Diego Muñoz-Torrero; Antoni Parcerisas; Antoni Camins; et al. (Cell & Bioscience, 2023)
Abstract Background Alzheimer’s disease (AD) is characterized by a polyetiological origin. Despite the global burden of AD and the advances made in AD drug research and development, the cure of the disease remains elusive, since any developed drug has demonstrated effectiveness to cure AD. Strikingly, an increasing number of studies indicate a linkage between AD and type 2 diabetes mellitus (T2DM), as both diseases share some common pathophysiological features. In fact, β-secretase (BACE1) and acetylcholinesterase (AChE), two enzymes involved in both conditions, have been considered promising targets for both pathologies. In this regard, due to the multifactorial origin of these diseases, current research efforts are focusing on the development of multi-target drugs as a very promising option to derive effective treatments for both conditions. In the present study, we evaluated the effect of rhein-huprine hybrid (RHE-HUP), a synthesized BACE1 and AChE inhibitor, both considered key factors not only in AD but also in metabolic pathologies. Thus, the aim of this study is to evaluate the effects of this compound in APP/PS1 female mice, a well-established familial AD mouse model, challenged by high-fat diet (HFD) consumption to concomitantly simulate a T2DM-like condition. Results Intraperitoneal treatment with RHE-HUP in APP/PS1 mice for 4 weeks reduced the main hallmarks of AD, including Tau hyperphosphorylation, Aβ42 peptide levels and plaque formation. Moreover, we found a decreased inflammatory response together with an increase in different synaptic proteins, such as drebrin 1 (DBN1) or synaptophysin, and in neurotrophic factors, especially in BDNF levels, correlated with a recovery in the number of dendritic spines, which resulted in memory improvement. Notably, the improvement observed in this model can be attributed directly to a protein regulation at central level, since no peripheral modification of those alterations induced by HFD consumption was observed. Conclusions Our results suggest that RHE-HUP could be a new candidate for the treatment of AD, even for individuals with high risk due to peripheral metabolic disturbances, given its multi-target profile which allows for the improvement of some of the most important hallmarks of the disease.